Fetal Programming of Renal Dysfunction and High Blood Pressure by Chronodisruption - Mendez, Natalia; Torres-Farfan, Claudia; Salazar, Esteban; Bascur, Pía; Bastidas, Carla; Vergara, Karina; Spichiger, Carlos; Halabi, Diego; Vio, Carlos P.; Richter, Hans G. (Frontiers in Endocrinology, 2019)
Adverse prenatal conditions are known to impose significant trade-offs impinging on health and disease balance during adult life. Among several deleterious factors associated with complicated pregnancy, alteration of the gestational photoperiod remains largely unknown. Previously, we reported that prenatal manipulation of the photoperiod has adverse effects on the mother, fetus and adult offspring; including cardiac hypertrophy. Here, we investigated whether chronic photoperiod shifting (CPS) during gestation may program adult renal function and blood pressure regulation. To this end, pregnant rats were subjected to CPS throughout pregnancy to evaluate the renal effects on the fetus and adult offspring. In the kidney at 18 days of gestation, both clock and clock-controlled gene expression did not display a daily pattern, although there were recurrent weaves of transcriptional activity along the 24-h in the control group. Using DNA microarray, significant differential expression was found for 1,703 transcripts in CPS relative to control fetal kidney (835 up-regulated and 868 down-regulated). Functional genomics assessment revealed alteration of diverse gene networks in the CPS fetal kidney, including regulation of transcription, aldosterone-regulated Na+ reabsorption and connective tissue differentiation. In adult offspring at 90 days of age, circulating proinflammatory cytokines IL-1β and IL-6 were increased under CPS conditions. In these individuals, CPS did not modify kidney clock gene expression but had effects on different genes with specific functions in the nephron. Next, we evaluated several renal markers and the response of blood pressure to 4%NaCl in the diet for four weeks (i.e. at 150 days of age). CPS animals displayed elevated systolic blood pressure in basal conditions that remained elevated in response to 4%NaCl, relative to control conditions. At this age, CPS modified the expression of Nhe3, Ncc, Atp1a1 and glucocorticoid and mineralocorticoid receptors; while Nkcc, Col3A1 and Opn were modified in the CPS 4%+NaCl group. Furthermore, CPS decreased protein expression of Kallikrein and COX-2, both involved in sodium handling. Finally, CPS conditions decreased genomic DNA methylation in the adult kidney, suggesting programming through epigenetic mechanisms. In conclusion, gestational chronodisruption programs kidney dysfunction at different levels, conceivably underlying the prehypertensive phenotype observed in the adult CPS offspring.